Reading Proclus and the Book of Causes, Volume 2 Translations and Acculturations - Calma, Dragos (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2020)
Reading Proclus and the Book of Causes, published in three volumes, is a fresh, comprehensive understanding of the history of Neoplatonism from the 9th to the 16th century. The impact of the Elements of Theology and the Book of Causes is reconsidered on the basis of newly discovered manuscripts and evidences. This second volume revises widely accepted hypotheses about the reception of the Proclus' text in Byzantium and the Caucasus, and about the context that made possible the composition of the Book of Causes and its translations into Latin and Hebrew. The contributions offer a unique, comparative perspective on the various ways a pagan author was acculturated to the Abrahamic traditions. Readership: All interested in the history of philosophy, Late Antiquity, Arabic Philosophy, Jewish Philosophy, Scholasticism, Byzantine Philosophy.